Growth Mindset dan Aktualisasi Diri pada Mahasiswa Yogyakarta - Maharani Nur Annisaa; Narastri Insan Utami (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The rapid growth of higher education in Indonesia highlights the importance of understanding personal factors that support students’ potential development. Grounded in mindset and self-actualization theories, this study aims to examine the relationship between growth mindset and self-actualization among university students in Yogyakarta. This research employed a quantitative correlational design involving 124 students aged 18–24 years from various public and private universities selected through total sampling. The instruments used were the Growth mindset Scale (Chen, Ding, & Liu, 2021; Indonesian adaptation) and the Self-Actualization Scale adapted from Pratiwi (2003). Both instruments demonstrated strong psychometric properties after item validation (17 items for growth mindset and 53 items for self-actualization). Data analysis using SPSS 22.0 for Windows included normality testing and linearity testing, confirming that the data met parametric assumptions. The results of the Pearson product–moment correlation revealed a positive and significant relationship between growth mindset and self- actualization (r = .638, p < .001). This indicates that students with higher growth mindset levels tend to exhibit greater self-actualization. The findings reinforce the theoretical notion that a growth-oriented belief system fosters persistence, self- awareness, and optimal self-development in academic contexts. Practical implications emphasize the need to integrate growth mindset–enhancing strategies into both curricular and extracurricular programs, including workshops, mentoring, and organizational activities that promote continuous personal growth.